Analysis Of Sighat Transactions in Marketplace (Islamic Perspective on E-Commerce Behavior) - Betania Kartika; Siti Aisyah; Mutiara Rahmah (Journal of Management and Business Innovations, 2023)
This study discusses the practice of selling and buying transactions in the marketplace. In this implementation, there is often no sighat/contract, and the sacredness of the contract is lost, which raises questions about the legitimacy of buying and selling activities in Islam's Perspective. This study used qualitative methods, as well as using the library research method, which is a set of related activities by collecting data, reading, and recording research sources related to research and processing problems, namely the analysis of buying and selling practices without a contract or sighat in modern society especially marketplace. The purpose of this study is to show the habits of modern society in buying and selling, not making a contract but doing actions that show an agreement on both sides. The results of this discussion are the habits of modern society in the practice of buying and selling, not making contracts due to the development of technology, and many people who want to be simple in buying and selling.Keywords: 'urf, behavior, contract, marketplace, sighat